The effects of advertising expenditure towards China's money demand - Yusuf Roy Fitri, B. Mohd Johnny (Universiti Malaysia Sarawak (UNIMAS), 2012)
This study aims to shed some light in identifying the possible determinants of the money demand function in China in order to generate a credible and well-defined money demand function by using the appropriate data analysis and econometric tools between the period of 2000:Q1 to 2009:Q4. Apart from that, this study also aims to determine the relationship between the specified macroeconomic variables as well as to identify the incurrence of advertising expenditure in the money demand of China.